1986
DOI: 10.1080/00050068608256914
|View full text |Cite
|
Sign up to set email alerts
|

What would I do if I couldn't do what I wanted to do? investigating career compromise strategies

Abstract: Although the process of compromise is crucial to career decision making, it has received little attention. This paper reports an attempt to explore people's attitudes and beliefs about how they would behave if they were forced to make career compromises. Specifically, subjects were asked to indicate what they would do if they were faced with a number of hypothetical career compromise situations where there were limited alternatives. Each alternative represented a different strategy and was varied according to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
2

Year Published

1989
1989
1998
1998

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 11 publications
0
9
2
Order By: Relevance
“…For example, Leung and Plake (1990) reported that prestige level was not compromised to maintain gender traditionality by college students as is predicted. However, contrary to the findings of Leung and Plake (1990), Pryor and Taylor (1986) found that prestige level was typically compromised to maintain interests and sex type, though this pattern does not fully follow Gottfredson's predictions either. In a study by Hesketh, Elmslie, and Kaldor (1990) with both career dissatisfied adults and high school students, interests were rated as more important than level of prestige, and prestige was rated as more important than level of sex type, a pattern directly opposite the pattern Gottfredson predicts.…”
Section: Research On Gottfredson's Theorycontrasting
confidence: 94%
See 1 more Smart Citation
“…For example, Leung and Plake (1990) reported that prestige level was not compromised to maintain gender traditionality by college students as is predicted. However, contrary to the findings of Leung and Plake (1990), Pryor and Taylor (1986) found that prestige level was typically compromised to maintain interests and sex type, though this pattern does not fully follow Gottfredson's predictions either. In a study by Hesketh, Elmslie, and Kaldor (1990) with both career dissatisfied adults and high school students, interests were rated as more important than level of prestige, and prestige was rated as more important than level of sex type, a pattern directly opposite the pattern Gottfredson predicts.…”
Section: Research On Gottfredson's Theorycontrasting
confidence: 94%
“…Prestige and interests were found to be equivalent in stability for women over a one year period for all participants and for those who changed occupational aspirations from year one to year two, and when compromise was reported prestige was actually found to be less stable than the Things/People dimension of interests for women. Pryor and Taylor (1986) also found that prestige was sacrificed to maintain interests, and Hesketh, Elmslie & Kaldor (1990) and Hesketh, Durant & Pryor (1990) both found that interests were more important than prestige in their studies. Considerable evidence contradicting the order of compromise as predicted by Gottfredson has begun to accumulate.…”
Section: People-things As a Gendered Dimensionmentioning
confidence: 96%
“…On the research level, a variety of possible empirical studies arise from Gottfredson's circumscription/compromise formulation of I98 1. In our view, the two most crucial are: the need to be able to measure individuals' cognitive maps of occupations - Gottfredson (1985) acknowledges this as a major shortcoming of her theory; and the investigation of the process of compromisewe have tried to make a start in researching this area using Gottfredson's theory as a basis (Pryor & Taylor, 1986;Taylor & Pryor, 1985).…”
Section: Resultsmentioning
confidence: 99%
“…The traditional view of career compromise has focused on the discrepancy between the individuals' characteristics and the characteristics of the available opportunities (Ginzberg, Ginsburg, Axelrad, & Herma, 1951), or between self-concept and reality (Super, 1953). Following Gottfredson's (1981) circumscription and compromise theory, there has been a renewed interest in compromise (e.g., Hesketh, Elmslie, & Kaldor, 1990;Leung & Harmon, 1990;Pryor, 1987;Pryor &Taylor, 1986,1989Taylor & Pryor, 1985). In this article, we discuss a conceptual model for career compromise which is based on concepts adapted from decision theory (Brown, 1990;Gati, 1986;Jepsen & Dilley, 1974;Mitchell & Krumboltz, 1984;Phillips, 1994;Pitz & Harren, 1980, Slaney, 1988Walsh & Osipow, 1988).…”
mentioning
confidence: 99%